2020
DOI: 10.3897/folmed.62.e49815
|View full text |Cite
|
Sign up to set email alerts
|

Large-cell Neuroendocrine Carcinoma of the Endometrium in Myomatous Uterus

Abstract: Large-cell neuroendocrine carcinoma of the endometrium is an insufficiently researched aggressive tumor with a short survival regard­less of the treatment type. We present here the 38th consecutive case of literature reported cases of large cell neuroendocrine carcinoma of the endometrium (posi­tive for synaptophysin, CD56, chromogranin A, p53, and Vimentin) found in the myomatous uterus of a 76-year-old woman. We also describe in the study the morphological algorithm for di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…This multicenter study suggested that stage III-IV disease and pure SCNEC are associated with significantly poorer prognosis than other disease stages and histological types. However, some studies have reported long-term survival in patients with advanced disease (10,12,16) SCNEC treated with surgery + CT (cisplatin + etoposide) + RT, and their patient remained alive 5 years later. The current study included the largest cohort of patients with NETs of the endometrium to date.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This multicenter study suggested that stage III-IV disease and pure SCNEC are associated with significantly poorer prognosis than other disease stages and histological types. However, some studies have reported long-term survival in patients with advanced disease (10,12,16) SCNEC treated with surgery + CT (cisplatin + etoposide) + RT, and their patient remained alive 5 years later. The current study included the largest cohort of patients with NETs of the endometrium to date.…”
Section: Discussionmentioning
confidence: 99%
“…This multicenter study suggested that stage III–IV disease and pure SCNEC are associated with significantly poorer prognosis than other disease stages and histological types. However, some studies have reported long-term survival in patients with advanced disease ( 10 , 12 , 16 ). Sawada et al.…”
Section: Discussionmentioning
confidence: 99%
“…10,12,13 These treatments were based on some data of small cell lung cancer, but there was no large-scale study or prospective clinical trial to guide the treatment of ENC. The commonly used chemotherapy regimens of NECA include etoposide and platinum drugs, 14,15 such as etoposide/cisplatin, carboplatin/paclitaxel. 12 Studies have shown that immediate surgery and chemotherapy were preferable to prolong disease-free survival and maintain a good performance status.…”
Section: Discussionmentioning
confidence: 99%